The Environment As A Legal Subject: A Post- Humanist Philosophical Perspective - Hyronimus Rhiti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The accelerating ecological crisis and the persistent anthropocentric orientation of legal systems have revealed significant limitations in traditional jurisprudence. Environmental degradation, climate change, and biodiversity loss underscore the urgency of rethinking legal frameworks that historically prioritize human interests over the rights and integrity of ecosystems. This study aims to explore the concept of the environment as a legal subject through the lens of post-humanist philosophy, emphasizing the ethical, ontological, and legal rationales for extending subjectivity beyond human entities. The research employs a philosophical and conceptual method, critically analyzing the theoretical foundations of legal subjectivity, post-humanist thought, and the moral standing of non-human entities. It synthesizes insights from legal philosophy, environmental ethics, and jurisprudence to construct a coherent framework for recognizing ecological systems as holders of rights within legal orders. The findings indicate that post-humanist philosophy provides a robust conceptual justification for acknowledging ecosystems as legal subjects. By decentering humans and emphasizing relationality among all living and non-living entities, law can be reoriented to protect the intrinsic value of nature, promote ecological sustainability, and ensure intergenerational justice. The study also identifies practical pathways for integrating ecological subjectivity into legal systems, including through the appointment of legal guardians for ecosystems and the adoption of rights-based frameworks in constitutional and statutory law. This research contributes to the theoretical discourse on environmental jurisprudence by offering a normative and philosophical basis for expanding the notion of legal subjectivity. It is expected to guide policymakers, scholars, and legal practitioners in developing laws that recognize the environment not merely as an object but as an active participant in legal and ethical frameworks.